Persen Lemak Tubuh dan Kebugaran Jasmani pada Atlet Sepak Bola - Putriana, Dittasari; Syula, Salsabila Ayu; Solichah, Kurnia Mar'atus (Avicenna: Jurnal Ilmiah, 2025)
Background: Physical fitness is of paramount importance for athletes, particularly for adolescent athletes, in order to achieve optimal physical performance. One element that has the capacity to influence an athlete's physical fitness is the composition of their body, specifically the body fat percentage. The objective of this study is to analyze the correlation between the body fat percentage and the physical fitness in adolescent football athletes. Method: This study was an observational analytical research used cross-sectional design. The sample for this study were 31 athletes from the PSS Development Center who were between the ages of 13-17 years old and willing to participate as respondents. The assessment of body fat percentage was obtained through direct measurement using a bioelectrical impedance analysis (BIA) scale. The data regarding the subjects' physical fitness was obtained from the PSS Development Center that be held in May of 2023 through the implementation of a bleep test. The analysis of the data was conducted using the Pearson correlation test, with a significance level of p<0.05. Results: The mean body fat percentage and the mean score of physical fitness were 13.69%±4.33 and 48.63±3.37, respectively. Seventy-seven percent of the athletes exhibited a normal percentage of body fat, while the remaining 100% athletes had excellent levels of physical fitness. Conclusion: There was no correlation between the body fat percentage and physical fitness among adolescent football athletes (p=0.5470; r=0.1125). Keywords: Body fat percentage, Physical fitness, athlete, adolescent, football